Significance of stigma receptivity in intergeneric cross-pollination of Salix × Populus - Elżbieta Zenkteler; Maria Katarzyna Wojciechowicz; Łukasz Zarychta (Acta Societatis Botanicorum Poloniae, 2016)
The pollen–stigma interaction plays an important role in reproductive process and has been continuously studied in many interspecific and intergeneric crossing experiments. The aim of this study was to investigate stigma receptivity (SR) of willow in order to determine the most suitable period for its pollination with poplar pollen and improve the effectiveness of Salix × Populus crosses. Tissue samples were examined histologically using light, epifluorescent, scanning, and transmission electron microscopy. Willow SR was determined by stigma morphological traits, test of pollen germination rate, Peroxtesmo test of peroxidase and esterase activity on stigma surface as well as papilla ultrastructure at anthesis. We have ascertained that the SR duration in willow is short, lasting from 1 to 2 DA. The poplar pollen germination rate on willow stigmas on 1 DA ranged from 26.3 to 11.2%.